Temporality lost: A feminist invitation to vertical writing that shakes the ground. (March 2023) - Helin, Jenny
Are we, as academics, stuck in a horizontal temporality, organised by the clock, that flattens our work, our words? In reading feminist work by Märta Tikkanen, Hélène Cixous, and others, a rupture strikes, establishing another temporality: vertical time. Is it possible, I ask, to learn from these authors and engage in academic writing in verticality? The answer is: Yes! Through an in-depth reading of special pieces, I see clearly that when we use our scholarly voice to write from within our vulnerabilities, it becomes possible to climb all the way up or dig ourselves deep down. In other words, we can 'go deep' in the sense of touching that which is most important, as well as finding ways to 'fly high, ' through writing. This shows that writing and temporality are always already interweaved with each other because writing produces temporalities just as temporality at play produces writing. In this writing-temporality meshwork, there seems to be no set genre for vertical writing. Rather, it consists of a multitude of practices, written in the instant, from within the urgency of articulating that which matters.